Digitalization as a driver of transformation towards sustainable performance in wine tourism: the Italian case - Festa, Giuseppe; Cuomo, Maria Teresa; Genovino, Cinzia; Alam, Gazi Mahabubul; Rossi, Matteo (Emerald Publishing, 2023)
Purpose:The main aim of this research was to investigate whether and how digitalization affects sustainability and performance in wine tourism. Design/methodology/approach: Based on the data emerging from the 2019 National Report on Wine Tourism from the National Association of “Wine Cities” in Italy (the most extreme case in the world of wine), three macro-agglomerates were investigated: digitalization, sustainability and performance, adopting descriptive and inferential statistics. Findings:Although rigorous correlation between adopted digitalization and performed sustainability on one side and performed sustainability and market performance on the other cannot be verified for the 92 wineries under investigation, there is visible evidence that the more digitalized wineries are, the more sustainable they become and the better their performance. Evidence was not found to support the idea that the more sustainable wineries are, the more they are digitalized and the better their performance. Research implications and limitations to theoretical and practical application have been discussed. Originality/value: Wine tourism, which is naturally associated with rural tourism, is a form of tourism in which sustainability has strong relevance, particularly considering the future needs/desires of post-pandemic tourists. At the same time, digitalization, especially in pandemic and post-pandemic tourism, is credited with developing a huge impact in this business, although wine tourism is most probably conceivable as a meta-market, with a strong cultural essence. In this respect, a digitalization > sustainability > performance approach seems practicable and globally profitable.